2012
DOI: 10.15557/jou.2012.0001
|View full text |Cite
|
Sign up to set email alerts
|

Normal and sonographic anatomy of selected peripheral nerves. Part I: Sonohistology and general principles of examination, following the example of the median nerve

Abstract: Ultrasonography is an established method for imaging peripheral nerves. It serves to supplement the physical examination, electromyography, and magnetic resonance imaging. It enables the identification of post-traumatic changes of nerves, neuropathies secondary to compression syndromes, inflammatory or neoplastic nerve lesions as well as the evaluation of postoperative complications. In certain situations, this technique is the imaging method of choice. It is increasingly used in anesthesiology for regional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 7 publications
1
24
0
9
Order By: Relevance
“…This, so-called "elevator technique", enables assessment of nerve shape, echogenicity, thickness and its relation with surrounding tissues (e.g. skin, muscles or vessels) (17). The correct identification of tibial motor nerve branches to the gastrocnemii, soleus and tibialis posterior muscles was checked by means of needle (70-mm, echogenic-coated, 22-gauge needle with length graduation) electrical stimulation (1 Hz frequency and 100 μs duration).…”
Section: Ultrasonographic Evaluationmentioning
confidence: 99%
“…This, so-called "elevator technique", enables assessment of nerve shape, echogenicity, thickness and its relation with surrounding tissues (e.g. skin, muscles or vessels) (17). The correct identification of tibial motor nerve branches to the gastrocnemii, soleus and tibialis posterior muscles was checked by means of needle (70-mm, echogenic-coated, 22-gauge needle with length graduation) electrical stimulation (1 Hz frequency and 100 μs duration).…”
Section: Ultrasonographic Evaluationmentioning
confidence: 99%
“…The nerve can be located, but visualization is poor and using this image for performing a nerve block would be very difficult. 3 An adequate view was obtained but a better image of the nerve might be desired for a nerve block. 4 A good view was obtained and the reviewer would feel comfortable performing a nerve block.…”
Section: Sample Sizementioning
confidence: 99%
“…Nerves that are difficult to visualize makes the procedure more challenging to perform and could potentially lead to complications, failure to perform the procedure, or decreased success. Prior research documents the common anatomical appearance of the target nerves by ultrasound in healthy subjects and in states of pathology such as neuropathy, nerve damage or disease [1][2][3][4]. These studies have identified that the echogenicity of nerves changes based on ratio of total fascicular area to whole nerve area and fascicle pattern [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to dynamic technological advances, ultrasound scans became one of the leading methods for diagnosing motor organs [47]. The advantage of MRI as compared to other techniques is the ability to assess bone marrow.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%